Hukum Memilih Pemimpin Non-Muslim dalam Syariah Islam - Nurkaidah Nurkaidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Leadership in Islam is a crucial issue. Even after the Prophet Muhammad (peace be upon him) passed away, the first thing his companions did was elect a successor, not a successor as a Messenger or Prophet, but as a caliph. The rule of law and the enforcement of justice without discrimination depend on the leader. Therefore, electing a leader is neither trivial nor easy, especially when the leader is a non-Muslim or infidel, while the majority of the people are Muslims. Sheikh Yusuf Qaradawi stated in his Contemporary Fatwa that when someone hammers a nail into a person's head to elect, they are testifying that that person is worthy of being a leader for the Muslims, and all will be held accountable by Allah SWT on the Day of Judgment.